2022
DOI: 10.1038/s41419-022-04612-3
|View full text |Cite
|
Sign up to set email alerts
|

The mmu_circRNA_37492/hsa_circ_0012138 function as potential ceRNA to attenuate obstructive renal fibrosis

Abstract: Circular RNAs (circRNAs) are involved in the pathogenesis of certain renal diseases, however, the function and mechanism of them in renal fibrosis remains largely unknown. In the present study, RNA expression data in unilateral ureteral obstruction (UUO) kidneys was obtained from our previous circRNA Microarray and public Gene Expression Omnibus datasets to construct a ceRNA network. The effects of target circRNA as long as the homologous human circRNA on renal fibrosis was examined in vitro and in vivo. Gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The immunofluorescence of puncta was performed following the standard process. Whole BUMPT cell or kidney tissue protein lysates were separated through SDS-PAGE, and then transferred to membrane and subsequently exposed to primary antibodies of RAGE, STAT3, p-STAT3, α-SMA, Collagen I/III, fibronectin, vimentin, and Atg7 following by the second antibody according to the standard procedure [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The immunofluorescence of puncta was performed following the standard process. Whole BUMPT cell or kidney tissue protein lysates were separated through SDS-PAGE, and then transferred to membrane and subsequently exposed to primary antibodies of RAGE, STAT3, p-STAT3, α-SMA, Collagen I/III, fibronectin, vimentin, and Atg7 following by the second antibody according to the standard procedure [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The OE of lncRNA 1700020I14Rik reduces the cell proliferation and expression of several genes (Col-4, FN, TGF-β1) associated with fibrosis by directly interacting with miR-34a-5p in a high glucose (HG) environment ( Li et al, 2018 ). Although circRNAs have been recognized as vital regulators in multiple diseases, few studies have revealed that the abnormal expressions of circRNAs are related to the RF ( Fan et al, 2021 ; Yi et al, 2021 ; Cheng et al, 2022 ). Hence, the role and regulatory mechanism of circRNAs in RF need urgently to be uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…The circRNAs can also act as a miRNA sponge to regulate gene expression, and be associated with occurrence and development of RF. It indicated that overexpression (OE) of circRNA_37492 attenuated the TGF-β1/UUO-induced RF via targeting the miR-7682-3p/Fgb axis, while the homologous hsa_circRNA_0012138, as a possible competing endogenous RNA (ceRNA), was speculated to regulate multiple gene expressions in RF, suggesting that the circRNA_37492/hsa_circ_0012138 might act as a potential therapeutic target for obstructive RF ( Cheng et al, 2022 ). The circRNA_30032 was mediated UUO-induced and TGF-β1-induced RF by sponging miR-96-5p to up-regulate the expression of profibrotic proteins, including FN, indicating that this cirRNA could induce RF via the miR-96-5p/HBEGF/KRAS axis ( Yi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are abundant in transcriptomes and participate in various biological activities by regulating transcription, splicing, mRNA stability, and translation. At present, many studies have investigated circRNAs as potential therapeutic targets for various diseases [45][46][47]. With the ongoing development of related research strategies and methods, many biological functions of circRNAs in animals have also been emerging, and circRNAs have been found to regulate the proliferation and differentiation of animal skeletal muscle cells by acting as ceRNAs and encoding small peptides[48].…”
Section: Discussionmentioning
confidence: 99%